Clinical Exercise Testing 2002
DOI: 10.1159/000062224
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cardiopulmonary Exercise Testing for Patients with Suspected Metabolic Myopathies and Other Neuromuscular Disorders

Abstract: Neuromuscular diseases (NMDs) can be associated with significant exercise limitation. As cardiopulmonary exercise testing (CPET) examines the integrated response to exercise, it has been investigated in multiple NMDs, proving itself particularly valuable in the evaluation of metabolic disorders, which exhibit typical patterns of exercise response. Disorders of carbohydrate metabolism usually demonstrate limitations of aerobic capacity and abnormalities of glycogen utilization. Lipid disorders seem to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Our patients also showed significantly lower maximum exercise capacity and peak compared to controls. Several studies evaluating exercise tolerance in MM have demonstrated markedly low peak ( 23 - 27 ), reflecting impaired muscle mitochondrial oxidative phosphorylation. The maximal exercise capacity of MM subjects has been shown to directly correlate with the degree of O 2 extraction in the impaired muscle, which enables the use of the systemic arterial to venous O 2 difference as a surrogate marker for mitochondrial oxidative capacity ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our patients also showed significantly lower maximum exercise capacity and peak compared to controls. Several studies evaluating exercise tolerance in MM have demonstrated markedly low peak ( 23 - 27 ), reflecting impaired muscle mitochondrial oxidative phosphorylation. The maximal exercise capacity of MM subjects has been shown to directly correlate with the degree of O 2 extraction in the impaired muscle, which enables the use of the systemic arterial to venous O 2 difference as a surrogate marker for mitochondrial oxidative capacity ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%